2013
DOI: 10.2174/15672026113109990003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Cerebral Aneurysm Formation and Rupture

Abstract: Oxidative stress is known to contribute to the progression of cerebrovascular disease. Additionally, oxidative stress may be increased by, but also augment inflammation, a key contributor to cerebral aneurysm development and rupture. Oxidative stress can induce important processes leading to cerebral aneurysm formation including direct endothelial injury as well as smooth muscle cell phenotypic switching to an inflammatory phenotype and ultimately apoptosis. Oxidative stress leads to recruitment and invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 112 publications
1
96
0
4
Order By: Relevance
“…29 Aoki et al 30 showed that ROSproducing genes were upregulated, and that ROS-eliminating genes were suppressed in CAs in mice, which indicated that overproduction of ROS occurred in aneurysm walls. Moreover, both a free radical scavenger (edaravone) and the deletion of ROS-producing gene (p47phox) effectively inhibited CA formation by suppressing inflammation in aneurysmal walls.…”
Section: Cerebral Aneurysms: An Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…29 Aoki et al 30 showed that ROSproducing genes were upregulated, and that ROS-eliminating genes were suppressed in CAs in mice, which indicated that overproduction of ROS occurred in aneurysm walls. Moreover, both a free radical scavenger (edaravone) and the deletion of ROS-producing gene (p47phox) effectively inhibited CA formation by suppressing inflammation in aneurysmal walls.…”
Section: Cerebral Aneurysms: An Inflammatory Diseasementioning
confidence: 99%
“…Moreover, both a free radical scavenger (edaravone) and the deletion of ROS-producing gene (p47phox) effectively inhibited CA formation by suppressing inflammation in aneurysmal walls. In a critical review of the literature on ROS, Starke et al 29 found that oxidative stress can induce important processes leading to CA formation including direct endothelial injury, SMC phenotypic modulation and apoptosis, recruitment and invasion of inflammatory cells through upregulation of chemotactic cytokines and adhesion molecules, and MMPs activation.…”
Section: Cerebral Aneurysms: An Inflammatory Diseasementioning
confidence: 99%
“…A mortalidade após HSA pode ser acima de 50%, e daqueles que sobrevivem, apenas 30-45% retornam aos seus empregos anteriores, e até 30% permanecem incapacitados. Os mecanismos exatos por trás da formação e ruptura do aneurisma não são claros, mas a inflamação e a degeneração tecidual são elementos-chave 7 .…”
Section: Discussionunclassified
“…Aluminum also interacts with calcium binding sites and disrupts calcium homeostasis and thereby induces neurodegeneration. The toxicity of Al was also found to be associated with reduced axonal length and dendritic branches in hippocampus [14,15].…”
Section: Modeling Stages Of Alzheimer's Disease In Ratsmentioning
confidence: 99%